The composition of hydrogels for cartilage tissue engineering can influence glycosaminoglycan profile - QG Wang; N Hughes; SH Cartmell; NJ Kuiper (European Cells & Materials, 2010)
The injectable and hydrophilic nature of hydrogels makes them suitable candidates for cartilage tissue engineering. To date, a wide range of hydrogels have been proposed for articular cartilage regeneration but few studies have quantitatively compared chondrocyte behaviour and extracellular matrix (ECM) synthesis within the hydrogels. Herein we have examined the nature of ECM synthesis by chondrocytes seeded into four hydrogels formed by either temperature change, self-assembly or chemical cross-linking. Bovine articular cartilage chondrocytes were cultured for 14 days in Extracel®, Pluronic F127 blended with Type II collagen, Puramatrix® and Matrixhyal®. The discriminatory and sensitive technique of fluorophore-assisted carbohydrate electrophoresis (FACE) was used to determine the fine detail of the glycosaminoglycans (GAG); hyaluronan and chondroitin sulphate. FACE analysis for chondroitin sulphate and hyaluronan profiles in Puramatrix® closely matched that of native cartilage. For each hydrogel, DNA content, viability and morphology were assessed. Total collagen and total sulphated GAG production were measured and normalised to DNA content. Significant differences were found in total collagen synthesis. By day 14, Extracel® and Puramatrix® had significantly more total collagen than Matrixhyal® (1.77±0.26 µg and 1.97±0.26 µg vs. 0.60±0.26 µg; p<0.05). sGAG synthesis occurred in all hydrogels but a significantly higher amount of sGAG was retained within Extracel® at days 7 and 14 (p<0.05). In summary, we have shown that the biochemical and biophysical characteristics of each hydrogel directly or indirectly influenced ECM formation. A detailed understanding of the ECM in the development of engineered constructs is an important step in monitoring the success of cartilage regeneration strategies.